Holistic Representations of Internal and External Face Features are Used to Support Recognition - Chan, Jessica Pui Kar; Ryan, Jennifer D. (Frontiers in Psychology, 2012)
Face recognition is impaired when changes are made to external face features (e.g. hairstyle), even when all internal features (i.e. eyes, nose, mouth) remain the same. Eye movement monitoring was used to determine the extent to which altered hairstyles affect processing of face features, thereby shedding light on how internal and external features are stored in memory. Participants studied a series of faces, followed by a recognition test in which novel, repeated and manipulated (altered hairstyle) faces were presented. Recognition was higher for repeated than manipulated faces. Although eye movement patterns distinguished repeated from novel faces, viewing of manipulated faces was similar to that of novel faces. Internal and external features may be stored together as one unit in memory; consequently, changing even a single feature alters processing of the other features and disrupts recognition.